Identifying Fraudulent Responses and Imposters in Research Recruitment of Subjects Through Social Media. - Webber-Ritchey, Kashica J.; Ally, Felisha; Galura, Sandra; Buck, Jacalyn; Brockway, Cindy; Chipps, Esther; Ponder, Tiffany; Simonovich, Shannon D.; Spurlark, Roxanne S.; Vancil, Barbara; Monturo, Cheryl (Journal of Nursing Administration (JONA))
OBJECTIVE: The aim of this study was to describe strategies to manage bots and frauds (B/F) during online recruitment of research subjects. BACKGROUND: Bots mimic human responses in surveys using sophisticated algorithms. Fraudulent responses occur when false or misleading information is provided to gain research incentives. This research team identified substantial issues with fraudulent responses and imposters. This issue has not been well reported in the literature. METHODS: Nurse managers recruited through social media completed an online survey in a national nurse-led research study. A gift card stipend was offered to participants for survey completion. An unexpected surge in survey responses prompted researchers to halt recruitment. Multiple B/F mitigation and data validation strategies were implemented to ensure data integrity and are discussed in this article. RESULTS: Of the 836 surveys, only 152 (18.2%) were complete and valid. CONCLUSIONS: When using social media for online research, incorporating preemptive mitigation strategies to combat B/F responses is essential.